Religious Moderation in Islamic Religious and Character Education Textbooks for Senior High Schools in Indonesia - Evi Fatimatur Rusydiyah; Saiful Jazil; Bassam Abul A’la; Rifqi Rahman (Global Journal of Islamic Education, 2025)
Issues of radicalism and intolerance are currently increasingly rampant in Indonesia, this is due to the condition of the nation with its own diversity, namely the diversity of tribes, cultures, regions, languages, and most importantly religion. Therefore, it is urgent to instill in students in the learning process about religious moderation materials to anticipate the emergence of radicalism and intolerance. The purpose of this study was to identify the content of Islamic religious education textbooks at the senior high school level in Indonesia about religious moderation and how the concept of religious moderation is contained in the textbook. The results of the study show that Islamic religious education textbooks at the senior high school level in Indonesia have included indicators of religious moderation with one theme, namely Morals. Based on quantity, the material on religious moderation in this Islamic religious education book is still small and still has great potential to be developed, but conceptually this book presents the instillation of a good mindset about morals or moral reasoning ability to deal with issues of religious moderation